Mayer-Rokitansky-Küster-Hauser Syndrome or uterus and vagina agenesis in a young patient - Juana Himilce Baralt Ross; Nélida Orozco Hechavarría; Eliecer Prades Hung (Centro Provincial de Información de Ciencias Médicas, 2018)
The case report of a patient with syndrome of Mayer-Rokitansky-Küster-Hauser or uterus and vagina agenesis, but with functioning ovaries, assisted by a multidisciplinary team in "Tamara Bunke Bider" Northern Maternal Hospital in Santiago de Cuba, whose diagnosis was carried out through the physical exam, the history of primary amenorrhoea and complementary studies as the cariotype and magnetic resonance of the pelvis is described.